The 'moral careers' of microbes and the rise of the matrons: an analysis of UK national press coverage of methicillin-resistant Staphylococcus aureus (MRSA) 1995-2006. - Crawford P; Brown B; Nerlich B; Koteyko N (Health, Risk & Society, 2008)
This paper examines similarities and differences in media discourses relating to methicillin resistant Staphylococcus aureus (MRSA) at three important points in the development of the bacterium and its perception by the public over the last decade. We analyse three increasingly large sets of texts from the national media using a variety of complementary qualitative and quantitative methods. As such this paper exploits, develops and empirically assesses an emerging methodological trend in applied linguistics, namely the convergence of critical metaphor analysis, with corpus linguistics and science and technology studies. Using this, the study identifies a shifting media narrative that involves changes in dramatis personae over the decade. First, personified forces of nature, doctors and hospitals are engaged in a battle of evil against good, but also intelligence over stupidity. Second, we are presented with victims of personified bacterial forces and doctors and hospitals cast as perpetrators of crimes of omission by not cleaning hands or wards. Third, the malignant forces of politics try to exploit the evil forces of nature for their own ends while a mediator between the doctors and the potential victims of MRSA emerges and is given political and symbolic power: the modern matron.